Use of plant-derived products to control household and structural arthropod pests - Gahukar, Ruparao (International Journal of Basic and Applied Sciences, 2017)
Plant extracts in water or chemical solvents; crude oil, essential oils and other allelochemicals of several plant species were tested at the laboratory as contact poison and/or fumigant. Most of them acted as repellent to insects and mites. Toxicity effect was dose-dependent and varied as per plant species and organism tested. In some instances, plant-derived products causing mortality were less effective than synthetic pesticides. However, considering possible environmental contamination of synthetics and the eventual toxicity to non-target organisms, plant-derived products against household and structural pests have been recommended by researchers. The major pest species with mode of actions of plant products and integrated strategies for effective, practical and ecofriendly pest control are discussed throughout this review.
Keywords: Allelochemicals; Insects; Mites; Plant Extracts; Mode of Action; Household and Structural Pests.